Kejahatan Penipuan Jual Beli Online Melalui Media Sosial - Fauzi, Achmad; Wibowo Noor Fikri, Adi; Marhadi, Arif; Arif Prabaswara, Bagas; Benyamin Situmorang, Benny; Anggraeni Piliyanto, Elsa; Adilah Nasution, Intan; Eka Nugraha, Raffi (Dinasti Review, 2023)
This research is titled “Online Social Media Fraud in Buying and Selling: The role of Social media and crime prevention methods. “Its aim is to determine the extent of the role and influence of social media in fraudulent activities and to identify ways to prevent online fraud in buying and selling. The research methodology employed is qualitative, using a literature review approach to gather information from articles and online journals. The findings of the study describe the role and influence of social media in cases of fraudulent transactions in online platforms, as well as prevention methods and relevant laws governing information and electronic transactions.